DPP-4-inhibitors - What are the similarities, where are the differences? - Blüher, Matthias (Forum diabetologicum, 2012)
With the increasing prevalence of type 2 diabetes and its complications throughout the world, there is a need for efficient and safe therapeutic strategies. The dipeptidyl peptidase-4 (DPP-4) inhibitors have become important oral glucose lowering drugs for the management of patients with type 2 diabetes. All DPP-4-inhibitors act on the incre - tin system to lower hyperglycemia, have a similar safety profile, are well tolerated, do not cause significant weight gain and have a relatively low risk of hypoglycemia. However, there are clinical differences among the four agents, sitagliptin, vildagliptin, saxagliptin, and linagliptin which are currently approved by the US Food and Drug Admi - nistration or the European Medicines Agency. This review article discusses similarities and differences in efficacy, safety and tolerability of these four DPP-4-inhibitors.
Keywords: Hypoglycemia; Humans; Glucagon-Like Peptide 1; hyperglykemie; Incretins; Diabetes Mellitus, Type 2; hypoglykemie; inkretiny; vztahy mezi strukturou a aktivitou; glukagonu podobný peptid 1; hodnocení léčiv; Hyperglycemia; Drug Evaluation; diabetes mellitus 2. typu; lidé; inhibitory dipeptidylpeptidasy 4; Dipeptidyl-Peptidase IV Inhibitors; Structure-Activity Relationship